ANTIBACTERIAL EFFECTIVENESS OF WATER HYACINTH (Eichhornia crassipes) LEAF EXTRACT ON THE GROWTH OF Porphyromonas gingivalis - Laili Nurul Islami; Beta Widya Oktiani; Yusrinie Wasiaturrahmah (Universitas Lambung Mangkurat, 2023)
Background: The most common periodontal disease is periodontitis which is frequently found in the form of chronic periodontitis. Such disease is caused by the accumulation of the bacterium Porphyromonas gingivalis where supporting therapy such as chlorhexidine gluconate mouthwash 0.2% can be given. However, its use in the long term can have a negative effect on the oral cavity. There is a natural plant, namely water hyacinth (Eichhornia crassipes) which contains compounds that can be used as antibacterial, such as: tannins, phenols, flavonoids, alkaloids, saponins, terpenoids, and steroids. As a result of this, the water hyacinth plant can be used as an alternative herbal medicine. Purpose: To analyze the antibacterial effectiveness of water hyacinth leaf extract (Eichhornia crassipes) against the growth of Porphyromonas gingivalis bacteria. Methods: This study used True Experimental with posttest only with control group design. Antibacterial test was performed using liquid dilution method to determine MIC and solid dilution to determine MBC. Results: Based on the results and data analysis, it was found that the water hyacinth leaf extract had MIC at 1,56% and MBC at a concentration of 50%. Conclusion: Leaf extract of water hyacinth (Eichhornia crassipes) can inhibit and have antibacterial properties against the growth of Porphyromonas gingivalis bacteria. Keywords: Chronic periodontitis, Leaf extract of Water Hyacinth, Porphyromonas gingivalis